Analisis Strategi Promosi Melalui Pemanfaatan Media Sosial Instagram dalam Meningkatkan Penjualan pada Bitween Coffee Surabaya - Vania Regita Lailia; Acep Samsudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine promotion strategies through the utilization of Instagram social media in increasing sales at Bitween Coffee Surabaya. This research uses descriptive qualitative research methods. The research was conducted at Bitween Coffee Surabaya. The subjects of this study include the owner, employees, and consumers of Bitween Coffee Surabaya. Data sources will be collected using data collection techniques such as interviews, observations, documentation, and triangulation. The collected data will then be analyzed using data reduction techniques, data presentation, and drawing conclusions. The results of this study reveal that Bitween Coffee Surabaya employs a promotion strategy based on the 4C concept, which includes Context, Communication, Collaboration, and Connection. Bitween Coffee Surabaya also makes various efforts to optimize its promotion strategy through Instagram social media. These efforts include creating an attractive Instagram profile, generating visually appealing content, utilizing Instagram stories and reels, using popular hashtags, actively engaging with customers, organizing contests, collaborating with influencers, monitoring content using analytics tools, and partnering with other businesses.